President Abdurrahman Wahid’s Efforts to Consolidate the Democratic Transition from the Soeharto Authoritarian Regime - Saefur Rochmat (Insaniyat : Journal of Islam and Humanities, 2017)
Abdurrahman  Wahid  was  appointed  by  MPR  (the  Indonesian  People’s  Representative  Assembly) as  the  President  of  the  Republic  of  Indonesia  because  of  his  idea  of  democracy,  convincing  the prevailing  two  opposing  groups,  namely  the  nationalist  groups  and  Islamist  groups  (it  is  well- known as Poros Tengah/ the Central Axis). Indeed, he was able to adapt democracy to the Islamic tradition by employing the fiqh-plus paradigm to the relationship between Islam and the state. He made uses of the presidential office to consolidate the democratic transition such as by supporting civil society, establishing civil supremacy and establishing law enforcement. From beginning it was not  easy  for  him  to  socialise  his  fiqh-plus  paradigm  to  other  Islamic  groups.  Moreover,  Central Axis, the determining force contributing to the win of Wahid’s presidential election, felt upset with Wahid’s policies which did not align with their interests. The nationalist groups were also anxious about  occupying  the  presidential  office  for  themself.  Last  but  not  the  least,  the  military  also agreed with the idea of impeachment of President Wahid in order to save their political interests.DOI: 10.15408/insaniyat.v1i2.5473